Diagnostic and prognostic value of circulating microRNAs in patients with acute chest pain. (27th March 2014) - Devaux, Y.; Mueller, M.; Haaf, P.; Goretti, E.; Twerenbold, R.; Zangrando, J.; Vausort, M.; Reichlin, T.; Wildi, K.; Moehring, B.; Wagner, D. R.; Mueller, C.
Abstract Objectives To address the diagnostic value of circulating microRNAs (miRNAs) in patients presenting with acute chest pain. Design In a prospective, international, multicentre study, six miRNAs (miR‐133a, miR‐208b, miR‐223, miR‐320a, miR‐451 and miR‐499) were simultaneously measured in a blinded fashion in 1155 unselected patients presenting with acute chest pain to the emergency department. The final diagnosis was adjudicated by two independent cardiologists. The clinical follow‐up period was 2 years. Results Acute myocardial infarction (AMI) was the adjudicated final diagnosis in 224 patients (19%). Levels of miR‐208b, miR‐499 and miR‐320a were significantly higher in patients with AMI compared to those with other final diagnoses. MiR‐208b provided the highest diagnostic accuracy for AMI (area under the receiver operating characteristic curve 0.76, 95% confidence interval 0.72–0.80). This diagnostic value was lower than that of the fourth‐generation cardiac troponin T (cTnT; 0.84) or the high‐sensitivity cTnT (hs‐cTnT; 0.94; both P < 0.001 for comparison). None of the six miRNAs provided added diagnostic value when combined with cTnT or hs‐cTnT (ns for the comparison of combinations vs. cTnT or hs‐cTnT alone). During follow‐up, 102 (9%) patients died. Levels of MiR‐208b were higher in patients who died within 30 days, but the prognostic accuracy was low to moderate. None of the miRNAs predicted long‐term mortality. Conclusion The miRNAs investigated in this study do not seem to provide incremental diagnostic or prognostic value in patients presenting with suspected AMI.